Community engagement strengthens pig disease knowledge and passive surveillance in Timor-Leste - Millar, Joanne; Morais, Olavio; Da Silva, Henriqueta; Hick, Paul; Foster, Ayrial; Jong, Joanita Bendita da Costa; Pereira, Abrao; Ting, Shawn; da Conceição, Felisiano; Toribio, Jenny-Ann L. M. L. (Frontiers in Veterinary Science, 2023)
Smallholder pig production in Timor-Leste is culturally and economically important for most households. However, regular and ongoing disease surveillance and pig husbandry training to farmers is limited. This paper describes collaborative social and diagnostic research followed by a pilot community engagement program to improve farmer and veterinary knowledge, skills and working relationships. There were three phases; 1) A qualitative study in 2020 to explore experiences and knowledge of 133 pig farmers, 6 village leaders and 16 district veterinary technicians on pig diseases and reporting, treatment methods and access to information or assistance. 2) A pilot community engagement program in 3 villages in 2021 with diagnostic investigation with samples analysed from 27 dead adult pigs and 3) Evaluation of community engagement and training outcomes. Results of the qualitative study revealed limited reporting of sick or dead pigs by farmers to veterinary technicians due to lack of trust in the veterinary diagnostic system. Most technicians lacked experience with sampling or post-mortems so diagnostic training was undertaken for the pilot disease investigation. Evaluation results showed improved knowledge, motivation, and confidence of government staff and farmers. The credibility of veterinary technicians improved and gave them more confidence to work with communities. Farmers felt supported because all aspects of pig husbandry were addressed and they reported being more willing to report dead or sick pigs. The project indicates that improved passive disease surveillance can be achieved by engaging communities in smallholder pig farming in Timor-Leste. Further research and testing of the approach in other districts and countries is recommended.